A survey on the effects of Azithromycin in the treatment of gingival overgrowth induced by Cyclosporin in renal transplant patients - Kadkhoda Z.; Ataei R. (Tehran University of Medical Sciences, 2004)
Statement of Problem: Gingival overgrowth is a side effect commonly induced by Cyclosporin treatment. The effects of Azithromycin, a macrolidic antibiotic, has been focused on gingival enlargement treatment induced by cyclosporine in numerous articles. Purpose: The goal of the present study was to survey the effects of systemic Azithromycin in the treatment of gingival overgrowth induced by cyclosporine among renal transplant patients. Materials and Methods: In this clinical trial study, 18 renal transplant patients (6 females and 12 males) with gingival overgrowth were studied. Samples were randomly divided into two groups: case group were treated by systemic Azithromycin and controls were treated by systemic placebo. Periodontal parameters including bleeding on probing (BOP), clinical crown length (CL), periodontal pocket depth (PPD), gingival overgrowth (GOI) and stent-IDP (vertical distant between a stent or plate with teeth occlusal planes at least from three of the most anterior contact points to mesial papillae) before treatment, two and six weeks after treatment were measured. To analyze the data, Wilcoxon and Mann-Whitney tests were used. Results: Most of the measured indices, among case and control groups, were significantly improved, after two weeks (P<0.05). No statistically significant differences were found between two groups except for BOP index (P<0.05). In other words, more BOP improvement was observed in the case group after six weeks comparing to the control group. Conclusion: Considering the findings of this study, one can assume that the reported effects of Azithromycine on gingival overgrowth, induced by cyclosporine is somehow exaggerated and the effects attributed this medicine is probably inflammation reduction.